Biomarker Effects of Diesel Fuel Hydrocarbons Absorbed to PE-Plastic Debris on Mussel Mytilus trossulus - Nadezda Vladimirovna Dovzhenko; Victor Pavlovich Chelomin; Andrey Alexandrovich Mazur; Valentina Vladimirovna Slobodskova; Aleksandra Anatolyevna Istomina; Sergey Petrovich Kukla (Journal of Marine Science and Engineering, 2023)
Pollution of global oceans by plastic litter is one of the most important ecological problems of our time. At the same time, the active sorption of highly toxic chemicals dissolved in water by plastic also poses a threat to the marine environment and its inhabitants. This article presents the results of experimental studies on the properties of polyethylene (PE) as a vector of petroleum hydrocarbons (PH) and its influence on the biochemical parameters of tissues in the Pacific mussel Mytilus trossulus. It was shown that the presence of unused polyethylene fragments (PE) and PE fragments with water-soluble fractions of diesel fuel (PE-WSF-DF) in seawater caused the development of oxidative stress in M. trossulus. We observed severe changes in hemolymph lysosome membrane stability (LMS) and a significant increase in DNA fragmentation in the gills and digestive glands of mollusks. The presence of PE-WSF-DF fragments in water increased the activity of antioxidant enzymes: catalase (CAT) and glutathione-S-transferase (GST). In the experiment, direct contact between plastic fragments and mussels was excluded, meaning the filter-feeding mollusks ingested the desorbed PH and leaching components existing in PE from the water.